TO THE QUESTION OF IMPROVING ENERGY-SAVING AND ENVIRONMENTAL CHARACTERISTICS OF URBAN BUILDINGS - Ezhov, Vladimir Sergeevich; Semicheva, Natalia Evgenievna; Pakhomova, Ekaterina Gennadievna; Bredikhina, Natalia Vladimirovna; Emmanuel, Solomon (Journal of Applied Engineering Science, 2019)
A new structural material for the production of ventilated facades (ventilated fences) - granulated blast furnace slag, which has high structural, thermal and adsorption properties, allowing to significantly increase the energy-saving and environmental characteristics of ventilated fences and, accordingly, facades of buildings and structuresis described. Developed by the innovative design of ventilated facade (ventilated fencing) based on blast furnace slag, allowing the clear air of the street from a significant part of nitrogen oxides, sulphur oxides, oxides of carbon, soot particles and dust, to reduce the amount of heat delivered to the building in summer and heat loss in winter, which greatly improves the environmental and economic performance of buildings.